Molecular Catalysts : Structure and Functional Design. - Gade, Lutz H. (Wiley, 2014)
Highlighting the key aspects and latest advances in the rapidly developing field of molecular catalysis, this book covers new strategies to investigate reaction mechanisms, the enhancement of the catalysts' selectivity and efficiency, as well as the rational design of well-defined molecular catalysts. The interdisciplinary author team with an excellent reputation within the community discusses experimental and theoretical studies, along with examples of improved catalysts, and their application in organic synthesis, biocatalysis, and supported organometallic catalysis. As a result, readers will gain a deeper understanding of the catalytic transformations, allowing them to adapt the knowledge to their own investigations. With its ideal combination of fundamental and applied research, this is an essential reference for researchers and graduate students both in academic institutions and in the chemical industry. With a foreword by Nobel laureate Roald Hoffmann.